Characterization of Batumin Resistant Variants of Staphylococcus aureus Clinical Isolates - L. N. Churkina; S. I. Bidnenko; L. V. Avdeeva; L. V. Yaroshenko (Антибиотики и Химиотерапия, 2020)
Population analysis of 20 batumin susceptible staphylococcal strains, isolated from clinical materials allowed to detect resistant clones only in 3 strains. The frequency of batumin resistant variants isolation was low and depended on the antibiotic concentration. Resistance to batumin in 5 clinical strains and in 1 reference strain of Staphylococcus aureus ATCC 6538 P (209P) developed under laboratory conditions and induced significant phenotypic and chemotaxonomic changes in the pathogen. The variants, resistant to batumin, had the same degree of virulence for mice as the initial susceptible strain. The batumin resistant variants of S.aureus were unstable and on the medium without batumin completely restored their initial phenotype.